6-6a=-6-5a+5

Simple and best practice solution for 6-6a=-6-5a+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6a=-6-5a+5 equation:


Simplifying
6 + -6a = -6 + -5a + 5

Reorder the terms:
6 + -6a = -6 + 5 + -5a

Combine like terms: -6 + 5 = -1
6 + -6a = -1 + -5a

Solving
6 + -6a = -1 + -5a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5a' to each side of the equation.
6 + -6a + 5a = -1 + -5a + 5a

Combine like terms: -6a + 5a = -1a
6 + -1a = -1 + -5a + 5a

Combine like terms: -5a + 5a = 0
6 + -1a = -1 + 0
6 + -1a = -1

Add '-6' to each side of the equation.
6 + -6 + -1a = -1 + -6

Combine like terms: 6 + -6 = 0
0 + -1a = -1 + -6
-1a = -1 + -6

Combine like terms: -1 + -6 = -7
-1a = -7

Divide each side by '-1'.
a = 7

Simplifying
a = 7

See similar equations:

| 7/3x+2/5= | | 2x=77 | | y+.8=.6(y+4) | | 3+2x+5=-17 | | 3(2t+2)= | | y=0.2x^3-5 | | -2xb= | | 2m+9=90 | | f(x)=-4cos(x) | | 6y-16=90 | | f(-x)=7x^2+3x-8 | | 518=vot-16t^2 | | 5x+7=x-17 | | 518=vot-16t | | 6x-(2)=26 | | 5(x-2)=8x-x | | p=4x+450 | | 0.3X-1.8=-5.04 | | -10=3f+2f | | 14+7x-6-15x+5=5x+7-12x+5-12 | | S=c+xv | | 2y-4y=6 | | 29+4y-3=17y-14-5y | | (3x-6)=(x+10) | | 5k+12+k=x+28 | | 13f+6=-5 | | 2*(2a+3)=18 | | -9*2-3(-56+12*2)=78 | | u=7(3n+31)+9(n+1) | | =x^2+17x+72 | | -8+2x=-(x+4) | | (4x-20)=(3x) |

Equations solver categories